Beyond Systemic Lupus Erythematosus and Anti-Phospholipid Syndrome: The Relevance of Complement From Pathogenesis to Pregnancy Outcome in Other Systemic Rheumatologic Diseases - Cavalli, Silvia; Lonati, Paola Adele; Gerosa, Maria; Caporali, Roberto; Cimaz, Rolando; Chighizola, Cecilia Beatrice (Frontiers in Pharmacology, 2022)
Evidence about the relevance of the complement system, a highly conserved constituent of the innate immunity response that orchestrates the elimination of pathogens and the inflammatory processes, has been recently accumulated in many different rheumatologic conditions. In rheumatoid arthritis, complement, mainly the classical pathway, contributes to tissue damage especially in seropositive subjects, with complement activation occurring in the joint. Data about complement pathways in psoriatic arthritis are dated and poorly consistent; among patients with Sjögren syndrome, hypocomplementemia exerts a prognostic role, identifying patients at risk of extra-glandular manifestations. Hints about complement involvement in systemic sclerosis have been recently raised, following the evidence of complement deposition in affected skin and in renal samples from patients with scleroderma renal crisis. In vasculitides, complement plays a dual role: on one hand, stimulation of neutrophils with anti-neutrophil cytoplasmic antibodies (ANCA) results in the activation of the alternative pathway, on the other, C5a induces translocation of ANCA antigens, favouring the detrimental role of antibodies. Complement deposition in the kidneys identifies patients with more aggressive renal disease; patients with active disease display low serum levels of C3 and C4. Even though in dermatomyositis sC5b-9 deposits are invariably present in affected muscles, data on C3 and C4 fluctuation during disease course are scarce. C3 and C1q serum levels have been explored as potential markers of disease activity in Takayasu arteritis, whereas data in Behçet disease are limited to in vitro observations. Pregnancies in women with rheumatologic conditions are still burdened by a higher rate of pregnancy complications, thus the early identification of women at risk would be invaluable. A fine-tuning of complement activation is required from a physiological progression of pregnancy, from pre-implantation stages, through placentation to labour. Complement deregulation has been implicated in several pregnancy complications, such as recurrent abortion, eclampsia and premature birth; low complement levels have been shown to reliably identify women at risk of complications. Given its physiologic role in orchestrating pregnancy progression and its involvement as pathogenic effector in several rheumatologic conditions, complement system is an attractive candidate biomarker to stratify the obstetric risk among women with rheumatologic conditions.